Tensegriteta - Srpčič, Jan (Matrika, 2014)
Tensegrity is a neologism derived from the words tension and integrity. It is an umbrella term for constructions made from two sets of elements (relevant for this paper from cables and struts, connected with joints), which don't abide by Maxwell's condition for stiffness, but are nonetheless structurally sound. I will present two form-finding methods, along with their advantages and disadvantages.
Keywords: mechanics; mehanika; napetost; stiffness; tensegriteta; tensegrity; tension; trdnost